Odpowiedzi

2010-01-17T18:23:52+01:00
A)
x=4-3y
x+y=-6

x+3y=4
x+y=-6/× (-1)

x+3y=4
-x-y=6

2y= 10 / : 2
y=5

x+5=-6
y=5

x=-11
y=5

b)
-2x+y=-8 /× 2
4x-3y=2

-4x+2y=-16
4x-3y=2

-y=-14/× (-1)
y=14

-2x+14=-8
y=14

-2x=-22/: 2
y=14

x=11
y=14

c)
x+7y=22
y=5x-2

x+7y=22/× 5
-5x+y=-2

5x+35y=110
-5x+y=-2

36y=108
y=3

x+21=22
y=3

x=1
y=3
2010-01-17T18:28:05+01:00
ROZWIĄŻ METODĄ PRZECIWNYCH WSPÓLCZYNNIKÓW a)b)c)

a)x=4-3y
x+y=-6

x+3y=4
x+y=-6 całość mnożymy przez -1

x+3y=4
-x-y=6
________________ dodajemy
2y=10
y=5

podstawiamy do pierwszego
x=4-3y
x=4-15
x=-11



b)
-2x+y=-8 /mnożymy przez 2
4x-3y=2

-4x+2y=-16
4x-3y=2
____________
-y=-14
y=14

-2x+y=-8
-2x+14=-8
-2x=-8-14
-2x=-22
x=11


c)x+7y=22
y=5x-2

x+7y=22 /mnożymy przez 5
-5x+y=-2

5x+35y=110
-5x+y=-2
__________
36y=108
y=3

x+7y=22
x+21=22
x=22-21
x=1